Adopting Intercultural Scenarios in the English Classroom to Foster Oral Language Competence in Fourth Graders at Winston Churchill Public School during the Third Quarter 2018 - Cano Morales, Rodrigo (My University, 2018)
Achieving competent communication in a foreign language demands the implementation of learning strategies acknowledging cultural variations. This research provides new insights on how the teacher fosters oral communication strategies considering students’ cultural background and adopts intercultural scenarios to enhance language competence. Considering Costa Rican students, the fourth-grade class selected for the study integrates children from the United States, Venezuela, Mexico, Nicaragua, and China. Being a case study, this research follows a qualitative approach to obtain deep understanding on the contexts and details of the teaching-learning elements observed. The data collected showed that the activities and techniques applied in the classroom, such as contests, speeches, competitions and story dramatizations are effective and attractive to students. However, they still require improvements to overcome language barriers that negatively affect oral production and reduce both eagerness to participate and number of in-class oral interventions. If teachers incorporate students’ backgrounds in the activities, there is more chance for them to feel at ease; this way the culturally diverse collectivity becomes a more efficient vehicle to a successful learning process.
Rodrigo Cano Morales
Trabajo final de graduación